Discovery of Anti-Malarial Agents Through Application of In Silico Studies - A. Barmade, Mahesh; R. Murumkar, Prashant; Kumar Sharma, Mayank; P. Shingala, Kaushik; R. Giridhar, Rajani; Ram Yadav, Mange (Combinatorial Chemistry & High Throughput Screening, 2015)
Among the various parasitic diseases, malaria is the deadliest one. Due to the emergence of high drug resistance to the existing drug candidates there is a global need for development of new drug candidates which will be effective against resistant strains of malaria parasite. In silico molecular modeling approaches have been playing an important role in the discovery of novel lead molecules having antimalarial activity. Present review is an effort to cover all the developments related to the application of computational techniques for the design and discovery of novel antimalarial compounds since the year 2011 onwards.
Keywords: Antimalarial agents